Critical Review on Effect of 5G Technology on Covid-19 and Human Health Issues (Journal of Scientific Research, 2021)
This analytic research paper discusses the effects of emerging futuristic 5th Generation (5G) cellular technology over human health. The technology is growing with three major advantages of high speed, lower latency and to connect more devices at the same time. In the recent pandemic event of Covid-19, many believe that for the achievement of high speed in 5G, it will be required to have high power and this high power will decrease the immune system in short term. But actually, the reality doesn’t support the above condition. This paper defines how the speed will increase with the help of low bit error rate and also through different useful techniques thereby not just by increasing the power. In addition of high-frequency 5G radiation to an already complex mix of lower frequencies, the implementation will contribute to a negative public health outcome both from physical and mental health perspectives to a certain extent.